Has house price growth in Canadian cities been excessive? - Allen Head; Huw Lloyd-Ellis (Queen's University, Department of Economics, 2014)
The dramatic rise in Canada's average house price to average rent ratio has induced some commentators to argue that a speculative bubble is under way the collapse of which will have a calamitous effect on the economy. Others have argued, however, that the currently high level of house prices may be rationalized by the low cost of financing, given the decline in interest rates over the last two decades. In this article, we assess these arguments through the lens of a simple asset pricing model applied to city-level data. We quantify the etxent to which excess growth in Canadian house prices depends on the nature of the current regime governing real interest rates, expections of rent growth in different cities and variations in property taxes.
Keywords: E30; R31; R10; 330; house prices; interest rates